Gamification-assisted project-based learning in biology education: Critical thinking and collaboration among students in urban Medan, Indonesia - Damayanti Situmorang; Herbert Sipahutar (Biosfer: Jurnal Pendidikan Biologi, 2026)
In 21st-century learning, students are required to develop critical thinking and collaboration skills. Project-Based Learning (PjBL) integrated with gamification is considered a potential approach to support these competencies. This study aimed to examine the effect of gamification-assisted PjBL on Grade X students’ critical thinking and collaboration skills in the biodiversity topic at SMAN 21 Medan. The study employed a quasi-experimental method using a Non-Equivalent Control Group design, involving class X5 as the experimental group and class X7 as the control group selected through random sampling. Critical thinking skills were measured using ten essay questions representing five indicators, while collaboration skills were assessed through an observation sheet based on four indicators. The results showed a significant difference between the experimental and control groups. The t-test analysis of critical thinking skills yielded a significance value of 0.016 (< 0.05), with the experimental group achieving a higher posttest mean score (75.25) than the control group (61.60). Similarly, collaboration skills showed a significant difference with a significance value of < 0.001. These findings indicate that gamification-assisted PjBL has a positive effect on improving students’ critical thinking and collaboration skills compared to PjBL without gamification. Therefore, it is recommended that biology teachers integrate gamification elements such as points, badges, and challenges into project-based learning to enhance students’ critical thinking and collaboration skills.